The Uses of the Russian Onomatopoeic Interjection bats ‘bam, bang’ - Viimaranta, Johanna; Kanerva, Oksana (Institute of Slavic Studies, Polish Academy of Sciences, 2026)
Descriptions of Russian grammar have long acknowledged the possibility of using indeclinable onomatopoeic verbal interjections as predicates instead of verb forms. It has been suggested that this usage primarily replaces perfective (resultative) past tense verb forms of the same stem. We have analysed 470 examples from the Russian National Corpus to show that the interjection bats ‘bam, bang’ is not only used as a predicate. It is very often placed in positions where the verbs sharing the same stem (e.g. batsatʹ  ‘to bang repeatedly’ or ‘to bang once’) cannot be used. Many of the predicate uses are not timebound. Bats can also be used in describing sounds and their potential effects, even when no actual sound is involved.